2007
DOI: 10.1002/jez.b.21139
|View full text |Cite
|
Sign up to set email alerts
|

The search for non‐chordate retinoic acid signaling: lessons from chordates

Abstract: Signaling by retinoic acid (RA) is an important pathway in the development and homeostasis of vertebrate and invertebrate chordates, with a critical role in mesoderm patterning. Classical studies on the distribution of nuclear receptors of animals suggested that the family of RA receptors (RARs/NR1B) was restricted to chordates, while the family of RA X receptors (RXR/NR2B) was distributed from cnidarians to chordates. However, the accumulation of data from genome projects and studies in non-model species is q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
10

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 135 publications
1
28
0
10
Order By: Relevance
“…During animal development, RA is synthesized from retinol in two steps of NAD-dependent oxidation, each catalyzed by different families of enzymes ( Fig. 1b) (reviewed in Simões-Costa et al, 2008). After cellular uptake of ingested retinol by a system involving retinol binding protein (RBP) and the transmembrane protein STRA6 (Kawaguchi et al, 2007), the first step of RA synthesis is the reversible oxidation of retinol to retinal by enzymes of two different families: Only the major actors of the pathway (enzymes involved in retinoid synthesis, degradation, binding, and signaling) are shown.…”
Section: An Overview Over the Ra Signaling Cascadementioning
confidence: 99%
See 2 more Smart Citations
“…During animal development, RA is synthesized from retinol in two steps of NAD-dependent oxidation, each catalyzed by different families of enzymes ( Fig. 1b) (reviewed in Simões-Costa et al, 2008). After cellular uptake of ingested retinol by a system involving retinol binding protein (RBP) and the transmembrane protein STRA6 (Kawaguchi et al, 2007), the first step of RA synthesis is the reversible oxidation of retinol to retinal by enzymes of two different families: Only the major actors of the pathway (enzymes involved in retinoid synthesis, degradation, binding, and signaling) are shown.…”
Section: An Overview Over the Ra Signaling Cascadementioning
confidence: 99%
“…amphioxus and different tunicate species) provided evidence for roles of RA during development of all chordates (Cañ-estro and Postlethwait, 2007;De Bernardi et al, 1994;Denucé, 1991;Hinman and Degnan, 1998;Holland and Holland, 1996;Katsuyama et al, 1995). Moreover, recent studies have suggested a possible presence of this pathway in other deuterostomes: bioinformatic analyses have revealed rar, cyp26, and raldh homologs in the genome of the sea urchin Strongylocentrotus purpuratus and raldh and cyp26 homologs in EST sequences from the hemichordate Saccoglossus kowalevskii (Cañestro et al, 2006;Howard-Ashby et al, 2006;Marlétaz et al, 2006;Ollikainen et al, 2006;Simões-Costa et al, 2008).…”
Section: Evolutionary Origins Of Ra Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant role for RA signaling in the development of endoderm might appear somewhat surprising because endoderm is a germ layer of all multi-layered embryos, whereas the RA signaling system has often been described as a signaling system that has arisen during chordate evolution [3,4]. There is now, however, evidence that homologues of enzymes and receptors necessary for RA signaling exist in different invertebrates [5][6][7], but it is still not clear as to whether or not these homologues function in an analogous manner. If in fact they have alternate functions, then retinoic acid signaling may be an adaption that occurred during evolution and unique to the chordates.…”
Section: Introductionmentioning
confidence: 99%
“…Campo-Paysaa et al (2008) discuss the evolution of our views on retinoic acid (RA) signaling across animals. First considered a vertebrate-specific and then a chordate-specific system operating in the elaboration of the Anterior-Posterior axis, RA signaling is now increasingly perceived as an ancestral system that dates back to the bilaterian ancestor, owing to the characterization of some of its key players in the genomes of an echinoderm and one hemichordate, among deuterostomes, as well of a gastropod mollusk and an annelid, among protostomes (Campo-Paysaa et al 2008;Cañestro et al, 2006;Howard-Ashby et al 2006;Marlétaz et al, 2006a;Simões-Costa et al, 2008 and references therein; see also Albalat and Cañestro, 2008). Campo-Paysaa et al speculate that RA signaling may have played a role in neurite outgrowth and neuronal survival during development of the bilaterian ancestor, a role echoed by related actions of the RA in vertebrates and mollusks, but that it was subsequently lost in the lineage leading to ecdysozoan protostomes.…”
Section: Introductionmentioning
confidence: 99%